A new Ductile Iron for mechanically and thermally strained rolls Part 1: Simulation-based process characterization of hot rolling. (2nd November 2021) - Liepe, Martin; Duwe, Stephanie; Schrumpf, Martin; Bähr, Rüdiger; Tonn, Babette
ABSTRACT: When designing a new material for hot rolling rolls, it is necessary to be aware of the conditions in the later utilisation phase. The first step is to quantify stresses, and temperatures the material must tolerate operating in the rolling mills. These characteristics are evaluated by direct measurements and hot rolling simulations. Simulations targeted the identification of the temporal and spatial temperature distribution permeating the roll during the entire rolling process. As a major influence varying cooling conditions had to be accounted for roll temperatures. As an output value the minimum yield stress was identified – the determining factor for the development of a high strength roll material for cast rolls.